Pengaruh Citra Sekolah, Kualitas Pelayanan, dan Fasilitas Pendidikan Terhadap Kepuasan Siswa pada SMA Negeri 1 Percut Sei Tuan - Viona, Levvi; Tanjung, Yahya (Education Achievement: Journal of Science and Research, 2025)
The decision to stay overnight is one of the consumer's actions in choosing or The thesis entitled "The Influence of School Image, Service Quality, and Educational Facilities on Student Satisfaction at Sma Negeri 1 Percut Sei Tuan" is the result of quantitative research which aims to answer questions about the influence of school image, service quality, and educational facilities on student satisfaction. SMA Negeri 1 Percut Sei Tuan. The research methodology used is quantitative research using a sampling technique using simple probability sampling with a total of 92 respondents. The data collection technique uses a questionnaire processed using SPSS version 25. Data analysis uses multiple linear regression. Based on partial research results, the school image variable has a positive and significant effect on student satisfaction with a calculated t value of 3,558 > t table 1,662 and a significant value of 0.001 < 0.05, service quality has a positive and significant effect on student satisfaction with a calculated t value of 2,443 > t table 1,662 and a significant value of 0.017 < 0.05 and educational facilities have no effect on student satisfaction with a calculated t value of 0.333 < t table 1,662 and a significant value of 0.740 > 0.05 at SMA Negeri 1 Percut Sei Tuan. And simultaneously it shows that the variables of school image, service quality and educational facilities have a significant and positive effect on student satisfaction with a calculated f value of 38,167 > f table 2.71 and a significant value of 0.000 < 0.05.